Factor Xa inhibition by rivaroxaban regulates fibrogenesis in human atrial fibroblasts with modulation of nitric oxide synthesis and calcium homeostasis. (October 2018) - Chung, Cheng-Chih; Lin, Yung-Kuo; Chen, Yao-Chang; Kao, Yu-Hsun; Yeh, Yung-Hsin; Chen, Yi-Jen
Abstract: Background: Rivaroxaban, a widely used factor Xa inhibitor in reducing stroke in atrial fibrillation (AF) patients has multiple biological effects with activation of protease-activated receptor (PAR) signaling. Atrial fibrosis plays a critical role in the pathophysiology of AF. In this study, we evaluated whether rivaroxaban regulates atrial fibroblast activity and its underlying mechanisms. Methods and results: Migration, proliferation analyses, nitric oxide (NO) production assay, calcium fluorescence imaging, and western blots were conducted in human atrial fibroblasts with or without rivaroxaban (100 nmol/L or 300 nmol/L) and co-administration of L-NAME (L-NG-nitro arginine methyl ester, 100 μmol/L), EGTA (Ethylene glycol tetra-acetic acid, 1 mmol/L), thrombin (0.5 U/mL), PAR1 agonist peptide (TFLLR-NH2, 100 μmol/L), PAR1 inhibitor (SCH79797, 0.5 μmol/L) and PAR2 inhibitor (GB83, 10 μmol/L). Atrial fibrosis was examined in isoproterenol (100 mg/kg, subcutaneous injection)-treated rats with or without rivaroxaban (10 mg/kg/day orally for 14 consecutive days). Rivaroxaban reduced the migration, pro-collagen type I production, and proliferation of atrial fibroblasts. Rivaroxaban decreased phosphorylated endothelial NO synthase (eNOS) (Thr 495, an inhibitory phosphorylated site of eNOS), and calcium (Ca 2+ ) entry, and increased NO production. Moreover, L-NAME blocked the effects of rivaroxaban on fibroblast collagen and NO production. In the presence of EGTA, the migratory capability was similarly decreased in atrial fibroblasts with and without treatment with rivaroxaban (100 nmol/L), which suggests that rivaroxaban decreases migratory capability of atrial fibroblasts by inhibiting Ca 2+ entry. Additionally, rivaroxaban significantly attenuated the effects of thrombin, and TFLLR-NH2 on migratory, proliferative, and pro-collagen type I production capability in atrial fibroblasts. SCH79797 or GB83 decreased pro-collagen type I production, migration, and proliferation capability in fibroblasts, but combined SCH79797 or GB83 with and without rivaroxaban had similar fibroblast activity. Moreover, rivaroxaban significantly decreased atrial fibrosis in isoproterenol-treated rats. Conclusions: Rivaroxaban (100–300 nmol/L) regulates atrial fibroblast activity and atrial fibrosis by increasing NO production and decreasing Ca 2+ entry through inhibition of PAR signaling. Highlights: Rivaroxaban decreases the activity of human atrial fibroblasts. Rivaroxaban reduces Ca 2+ entry and increases NO production in atrial fibroblasts. Rivaroxaban attenuates the effects of thrombin or PAR agonists on fibroblasts Rivaroxaban reduces atrial fibrosis and atrial size in isoproterenol-treated rats. PAR 1, 2 signaling contributes to the effects of rivaroxaban on fibroblasts.